2021
DOI: 10.3390/jcm10030487
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of TNF and Non-TNF-Targeted Biologics on Body Composition in Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is associated with a decrease in lean mass and stability or even an increase in fat and ectopic adipose tissue. A few data are available on body composition changes under treatment, and data are still controversial. Body composition was assessed before initiation of biologic disease-modifying antirheumatic drug (bDMARD) and after 6 and 12 months of stable treatment. Eighty-three RA patients were included (75% of women, mean age 58.5 ± 10.8 years) of whom 47 patients treated with TNF i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…After this process, 32 articles were included for the full-text screening. Finally, after the full-text reading, we included nine studies: Engvall et al [ 41 ] and Marcora et al [ 42 ] as randomized clinical trials and Al Khayyad et al [ 43 ], Vial et al [ 44 ], Tournadre et al [ 45 ], Toussirot et al [ 46 ], Ferraz-Amaro et al [ 47 ], Metsios et al [ 48 ], and Chikugo et al [ 34 ] as observational studies. The search and inclusion/exclusion criteria are described in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After this process, 32 articles were included for the full-text screening. Finally, after the full-text reading, we included nine studies: Engvall et al [ 41 ] and Marcora et al [ 42 ] as randomized clinical trials and Al Khayyad et al [ 43 ], Vial et al [ 44 ], Tournadre et al [ 45 ], Toussirot et al [ 46 ], Ferraz-Amaro et al [ 47 ], Metsios et al [ 48 ], and Chikugo et al [ 34 ] as observational studies. The search and inclusion/exclusion criteria are described in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of the nine studies included, four of them were performed in France [ 42 , 44 – 46 ], one of them in the UK [ 48 ], one in Spain [ 47 ], one in Japan [ 34 ], one in Sweden [ 41 ], and one in Italy [ 43 ]. Studies included were published between 2007 and 2020.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…no significant changes in body composition) were reported with TNFα inhibitors in three small prospective studies ( n = 8–20) with various follow-up intervals (12 weeks to 2 years) and without control groups. 18 , 100 , 101 On the other hand, in a 1-year open follow-up study involving 83 RA patients (75% women; mean age 58.5 years; median disease duration 3.7 years), Tournadre et al 104 found significant changes in lean mass parameters in patients treated with TNFα inhibitors. In that study, the body composition parameters of 47 bDMARDs-naïve patients (mainly etanercept, n = 35) with active RA were compared with those of patients treated with csDMARDs alone ( n = 18) or with non-TNFα inhibitor bDMARDs ( n = 18 including 2 with tocilizumab, 10 with rituximab and 6 with abatacept).…”
Section: The Effect Of Treatments On Body Composition In Patients With Ramentioning
confidence: 99%
“…No change in body composition was observed at 12 months in patients treated with non-TNFα inhibitor bDMARDs or csDMARDs. 104 However, due to the lack of randomisation and the small sample size of the controls, no definitive conclusions can be drawn. Moreover, 45% of patients were on steroids (median dose 6.5 mg/day) with a heterogeneous distribution between the groups (72.2% in the non-TNF inhibitor bDMARDs group versus 38.3% in the TNF inhibitor groups versus 33.3% in the csDMARDs group).…”
Section: The Effect Of Treatments On Body Composition In Patients With Ramentioning
confidence: 99%